Earnings and Caste: An Evaluation of Caste Wage Differentials in the Nepalese Labour Market. - Mainali, Ram; Jafarey, Saqib; Montes-Rojas, Gabriel (Journal of Development Studies, 2017)
This paper examines the sources of wage differentials among castes in Nepal, a country which had, until 1963, an age-old caste-based social division of labour. We use an extended Oaxaca decomposition model with occupation and firm size augmenting the conventionally used measures of human capital endowments. Our results indicate that caste wage differentials in Nepal are large and that human capital endowments and lack of access to better paying occupations and larger firms have a significant impact. Furthermore, we find mixed evidence that the government policy of affirmative action has narrowed down the caste wage differential.